ANALISIS PENERAPAN STANDAR AKUNTANSI KEUANGAN PADA UMKM (COFFEE SHOP) DI KOTA PANGKALPINANG - Vermata Sari, Anggita; Tri Setyo Mulyani, Hendarti; Oktalina, Gayatria (Jurnal Akuntansi Bisnis Dan Keuangan, 2024)
This thesis was written by Anggita Vermata Sari with NIM 130190062, Faculty of Accounting. Title in Indonesian "Analysis of Application of Financial Accounting Standards to UMKM (Coffee Shop) in Pangkalpinang City". This research in the background by the application of financial accounting standards of EMKM has greatly influenced the success rate of UMKM Coffee Shop and is not fully employed by businessmen using EMKM SAK. (Coffee Shop). This study was conducted on 15 samples of Coffee Shop in Pangkalpinang City.This research is descriptive research using a qualitative approach. Data collection techniques by means of interviews, observations and documentation. Data analysis techniques by way of data collection, data reduction, data presentation and conclusion drawings. The results of this research are known that UMKM Coffee shop in Pangkalpinang city has not fully created or compiled financial reports using the application of SAK EMKM with the limitation of owners as well as employees who are not accounting/financial background and lack of socialization from the government so making financial reports in a simple way